Seasonal and age effects on in vitro embryo production in domestic cats under a standardized protocol - Priego-González, Andrea; Munoz-Maceda, Ana; Fuertes-Recuero, Manuel; Medranda Ayjon, Paula; Sánchez-Calabuig, María Aránzazu; Barroso-Arévalo, Sandra; Sánchez-Calabuig, María Jesús (Frontiers in Veterinary Science, 2025)
IntroductionIn vitro embryo production (IVP) in the domestic cat (Felis catus) remains highly variable owing to intrinsic reproductive traits and the absence of fully standardized protocols.MethodsWe retrospectively analysed 108 IVP replicates produced under a single protocol (2020–2024) to quantify the effects of season, donor age and methodological parameters on oocyte yield and embryo development.ResultsWinter proved the most favourable season for both oocyte recovery and blastocyst formation, whereas spring, despite lower initial yields, achieved the greatest post-selection oocyte retention. Donor age correlated negatively with oocyte number; however, older queens showed higher blastocyst conversion rates, suggesting that only developmentally competent oocytes persist at advanced age.DiscussionThese results highlight the need for rigorous donor selection and season-tailored IVP protocols to enhance embryo yield, quality and dataset reproducibility, prerequisites for deciphering embryo–maternal signalling mechanisms. Because the domestic cat serves as a valuable translational model for endangered felids, optimizing these factors will advance both feline ART and conservation breeding programs.